Looking queer: body image and identity in lesbian, bisexual, gay, and transgender communities - Atkins, Dawn (Haworth Press, 1998)
Looking Queer: Body Image in Lesbian, Bisexual, Gay, and Transgender Communities contains research, firsthand accounts, poetry, theory, and journalistic essays that address and outline the special needs of sexual minorities when dealing with eating disorders and appearance obsession. Looking Queer will give members of these communities hope, insight, and information into body image issues, helping you to accept and to love your body. In addition, scholars, health care professionals, and body image activists will not only learn about queer experiences and identity and how they affect individuals, but will also understand how some of the issues involved affect society as a whole. Dismantling the myth that body image issues affect only heterosexual women, Looking Queer explores body issues based on gender, race, class, age, and disability. Furthermore, this groundbreaking book attests to the struggles, pain, and triumph of queer people in an open and comprehensive manner. More than 60 contributors provide their knowledge and personal experiences in dealing with body image issues exclusive to the gay and transgender communities, including: exploring and breaking down the categories of gender and sexuality that are found in many body image issues finding ways to heal yourself and your community discovering what it means to “look like a dyke” or to “look gay” fearing fat as a sign of femininity determining what race has to do with the gay ideal discussing the stereotyped ”double negative”–being a fat lesbian learning strategies of resistance to societal ideals critiquing ”the culture of desire” within gay men’s communities that emphasizes looks above everything else Revealing new and complex dimensions to body image issues, Looking Queer not only discusses the struggles and hardships of gay, lesbian, bisexual, and transgendered persons, but looks at the processes that can lead to acceptance of oneself. Written by both men and women, the topics and research in Looking Queer offer insight into the lives of people you can relate to, enabling you to learn from their experiences so you, too, can find joy and happiness in accepting your body.
Section: li, 467 p
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; image corporelle; intersectionnalité; premier cycle; queer; régions géographiques; sciences humaines; soc2014; thématiques; troubles alimentaires; états-unis

Méthodologie féministe et anthropologie: une alliance possible - Dagenais, Huguette (Anthropologie et Sociétés, 1987)
Méthodologie féministe et anthropologie : une alliance possible Après un bref énoncé des principes épistémologiques et éthiques qui sous-tendent la recherche féministe et de la stratégie qui en découle dans la poursuite de projets concrets, l'auteure examine les affinités et apports réciproques entre anthropologie et méthodologie féministe puis souligne les contradictions profondes qui, selon elle, rendent problématique actuellement le développement de la recherche féministe en anthropologie. Elle termine en suggérant quelques pistes à suivre par les anthropologues féministes dans un proche avenir.
Keywords: 1900-1999; 1980-1989; amérique du nord; amériques; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; méthodologie; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques

Entre cri et chant: les katajjait, un genre musical féminin - Saladin d'Anglure, Bernard (Études Inuit Studies, 1978)
Le succès croissant en occident des différentes expressions graphiques ou plastiques de l'art inuit contemporain (ou préhistorique) a masqué d'autres aspects de l'art inuit, en particulier l'art musical traditionnel au sein duquel les jeux de gorge (notamment les katajjait) constituent un genre fascinant. Plusieurs des premiers voyageurs occidentaux qui y assistèrent en firent l'expérience à leurs dépens comme nous le verrons dans les documents qui suivent. Genre fascinant aussi pour l'anthropologue en raison de sa complexité et de son ambiguïté qui le font relever à la fois du cri et du langage, du chant et de la danse, du jeu et de la musique, du rite et de la performance; en raison également et de sa dimension symbolique lorsqu'il traite du rapport à la nature, du rapport au surnaturel et du rapport homme-femme, et de sa dimension sociologique à travers la coopération nécessitée par son exécution et la compétition parfois organisée entre les exécutants.
https://www.jstor.org/stable/42870488
Keywords: 1900-1999; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; amériques; anthropologie; chanson; discipline; genre; inuits; performance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines